Rationalization of servicing reefer containers in sea port area with taking into account risk influence - Filina-Dawidowicz Ludmiła (Polish Maritime Research)
This paper is aimed at presentation of a set of methods for rationalization of servicing containerized refrigerated cargoes in sea ports. During servicing reefer containers in port container terminals, take place various combinations of risk factors which can lead to loss of quality merits of cargoes contained in them. In the paper the risk factors capable of influencing quality of cargoes during their servicing in sea port, are identified, and the elaborated model for assessing risk level with the use of assumptions of fuzzy logic theory, is presented. Also, a simulation of servicing reefer containers in port, was performed. Moreover a prototype of an expert system which makes it possible to take correct decisions on servicing reefer containers in sea port, depending on impact level of risk factors, was proposed